Detoxification of soil and insurance herbicides in a chernozem typical in the left-bank Forest-Steppe of Ukraine - Demianiuk О.; Shatsman , D. (Quarantine and plant protection, 2019)
Goal. The content and detoxification rate of soil (Harnes, k.e.; Stomp 330, k.e.) and post emergent (Callisto 480 SC, KC; Milagro 040 SC, k.c.; Dianat, BRK; Esteron 60, k.e.) herbicides in chernozem typical of permanent corn cultivation technology was studied. Methods. By the method of gas-liquid chromatography, the content of active substances of herbicides in the soil. The mathematical methods established the half-life T50 of active ingredients of the preparations and detoxification rate constants (k) in a chernozem typical were established. Results. The studied herbicides had a rather high decomposition rate in the soil, and on the 45 day the content of their active substances was either not found or was 2.7—9.4% (Harnes, k.e., Dianat, BRK). The shortest half-life of T50 is specific for herbicides with active substances as nicosulfuron (4.6 days) and mesotrione (4.7 days), 2.4-Д 2-ethylhexyl ether (5.3 days) which indicates their low persistence in a chernozem typical and Milagro 040 SC, k.c., Callisto 480 SC, KC, Esteron 60, k.e. characterizes as moderately persistent. For herbicides with the active substance dicamba, pendamethalin and acetochlor, the half-life of T50 was maximum and in the amount to 11.6, 10.2 and 9.9 days, respectively. The biggest half-life of the active substance characterizes as the most stable and dangerous herbicides for the environment. Conclusions. It was confirmed that all the studied herbicides had enough high decomposition rate in the soil in corn agrocenosis. On the 45 day the herbicides Callisto 480 SC, KC, Milagro 040 SC, k.c., Esteron 60, k.e. completely decomposed in the soil, the herbicides Dianat, BRK, Harnes, k.e. — by 91% and 97%, respectively. For the rate constant of the detoxification process (k) in a chernozem typical the herbicides are placed in a row: Dianat, BRK > Stomp 330, k.e. > Harnes, k.e. > Esteron 60, k.e. > Callisto 480 SC, KC > Milagro 040 SC, k.c.